2018
DOI: 10.4103/ijo.ijo_939_17
|View full text |Cite
|
Sign up to set email alerts
|

Pars-plana fluid aspiration for positive vitreous cavity pressure in anterior segment surgeries

Abstract: Positive vitreous pressure due to misdirection of aqueous or choroidal effusion leads to shallowing of the anterior chamber (AC) before or during anterior segment surgeries. This shallow AC if not addressed makes surgery difficult and increases the risk of surgical complications. Methods to prevent and manage this condition described in literature are not without problems. We describe a minimally invasive technique of passing a 30G needle through the pars-plana to aspirate misdirected fluid from vitreous cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The study also indicated that in eyes with significant age-related liquefaction, where a 25G needle was expected to acquire a biopsy with 90% success; it was also possible to acquire a biopsy with a much smaller needle with similar success. This has only been explored previously in smaller studies or in substantially different clinical indications [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also indicated that in eyes with significant age-related liquefaction, where a 25G needle was expected to acquire a biopsy with 90% success; it was also possible to acquire a biopsy with a much smaller needle with similar success. This has only been explored previously in smaller studies or in substantially different clinical indications [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The similar performance of the 30G and 25G needles underscores the idea that formed vitreous, if present, is not well aspirated by needles of either gauge. Moving to 30G, because of its small cross-sectional area, will further ensure that formed vitreous cannot be aspirated [11]. Secondly, any vitreous strand that extends interiorly from the double-ended needle is very likely to be sheared when the sharp needle pushes through the tough septum of the drug cartridge, removing any vitreous 'anchor' on the interior of the device.…”
Section: Plos Onementioning
confidence: 99%
“…[ 3 4 ] In another approach, the liquefied vitreous is aspirated with a syringe through the pars plana. [ 5 6 ] These two approaches have both advantages and disadvantages. Despite the cost, the previous method has the advantage of always effectively reducing the IOP.…”
mentioning
confidence: 99%
“…The authors proposed a novel surgical technique to address a complex and vexing intraoperative complication commonly encountered in anterior segment surgeries. [1]…”
mentioning
confidence: 99%